1999
DOI: 10.1200/jco.1999.17.12.3793
|View full text |Cite
|
Sign up to set email alerts
|

Phase I/II Trial of IDEC-Y2B8 Radioimmunotherapy for Treatment of Relapsed or Refractory CD20+B-Cell Non-Hodgkin's Lymphoma

Abstract: These phase I/II data demonstrate that IDEC-Y2B8 radioimmunotherapy is a safe and effective alternative for outpatient therapy of patients with relapsed or refractory NHL. A phase III study is ongoing.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

10
256
3
7

Year Published

2002
2002
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 491 publications
(276 citation statements)
references
References 16 publications
10
256
3
7
Order By: Relevance
“…29 Both these CD20-targeted radioimmunoconjugates appear promising in the non-transplant setting. In early phase I/II studies, the maximum-tolerated dose of 90 Y ibritumomab was shown to be 0.4 mCi/kg, 30 with reversible hematological toxicity (principally thrombocytopenia) being the major side-effect. The same group has conducted a randomized trial prospectively comparing 90 Y ibritumomab (Zevalin) with rituximab, its 'naked' chimeric monoclonal antibody counterpart, in the setting of relapsed CD20-positive NHL.…”
Section: Radio-immunoconjugatesmentioning
confidence: 99%
“…29 Both these CD20-targeted radioimmunoconjugates appear promising in the non-transplant setting. In early phase I/II studies, the maximum-tolerated dose of 90 Y ibritumomab was shown to be 0.4 mCi/kg, 30 with reversible hematological toxicity (principally thrombocytopenia) being the major side-effect. The same group has conducted a randomized trial prospectively comparing 90 Y ibritumomab (Zevalin) with rituximab, its 'naked' chimeric monoclonal antibody counterpart, in the setting of relapsed CD20-positive NHL.…”
Section: Radio-immunoconjugatesmentioning
confidence: 99%
“…Although radiation protection issues mandate that therapy should be given as an inpatient in the UK, in most US states, outpatient administration is permitted (Siegel, 1998), and practical guidelines for such administrations are available (Siegel et al, 2002;Vose, 2004). Owing to concerns about Table 1 Properties of FDA approved RIT products available for therapy in B-cell NHL Modified from (Cheson, 2003) and (Stern and Herrmann, 2005) Results from the phase I/II dose escalation trial of Y 90 ibritumomab tixuetan, given in the format that we recognize as the commercial product administered today, were published in 1999 (Witzig et al, 1999). A previous phase I/II with Y 90 -labelled ibritumomab had used ibritumomab before the therapeutic infusion and dosing levels were escalated according to a flat level of total dose of between 20 and 50 mCi, with doses below 40 mCi being found to be nonmyeloablative (Knox et al, 1996).…”
Section: Tositumomabmentioning
confidence: 99%
“…A previous phase I/II with Y 90 -labelled ibritumomab had used ibritumomab before the therapeutic infusion and dosing levels were escalated according to a flat level of total dose of between 20 and 50 mCi, with doses below 40 mCi being found to be nonmyeloablative (Knox et al, 1996). The study of Witzig et al (1999), established that the maximum-tolerated dose was 0.4 mCi/Kg, reduced to 0.3 mCi/Kg in those with a baseline platelet count of between 100 and 149 Â 10 9 /l and replaced the unlabelled ibritumomab with rituximab 250 mg/m 2 given before the dosimetric or therapeutic infusions. In the 51 patients enrolled onto the study (36 on the phase II arm) the overall response rate (ORR) was 67%, with 26% of patients entering complete remission (CR).…”
Section: Tositumomabmentioning
confidence: 99%
“…This therapy targets the CD20 antigen present on most B-cell lymphomas and has been shown to be effective against low-grade and transformed low-grade NHL in both nonmyeloablative 3 and myeloablative (followed by autologous stem cell transplant) 4 protocols. Other RITs in development include another anti-CD20 MAb Y2B8 radiolabeled with yttrium-90, 5 Lym-1 (which targets the HLA-DR10 antigen on the surface of malignant B-lymphocytes) radiolabeled with iodine-131, 6 or copper-67 7 and LL2 (which targets the CD22 antigen on B-cell lymphomas) radiolabeled with iodine-131 8 or yttrium-90. 9 Initial RIT treatments were performed on an inpatient basis.…”
mentioning
confidence: 99%